Place Branding and Citizen Involvement: Participatory Approach to Building and Managing City Brands - Marta Hereźniak (International Studies: Interdisciplinary Political and Cultural Journal, 2017)
This article examines the role of citizens in the process of building and managing city brands. A multidisciplinary approach is applied to explain the multifaceted nature of territorial brands and citizen involvement. To this end, theoretical concepts from marketing and corporate branding, public management, and human geography are applied. By conceptualising place branding as a public policy and a governance process, and drawing from the concept of participatory place branding, the author discusses a variety of methods and instruments used to involve citizens. Special attention is given to the importance of modern technologies for effective citizen involvement.